Perinatal outcomes in second-trimester fetuses with isolated short femur - Ventura, Walter (2015)
Background: The finding of short femur (length below the 5th centile) at second trimester ultrasound examination is a diagnostic challenge. Classically, the short femur has been associated to chromosomal abnormalities and skeletal dysplasias. A few reports have been published on fetuses with isolated short femur outcomes. Objectives: To determine perinatal outcomes in the second-trimester fetuses with isolated short femur and to determine its association with fetal growth restriction. Design: Retrospective cohort study, also called historical or concurrent study. Setting: Fetal Medicine Unit, Instituto Nacional Materno Perinatal, Lima, Peru. Participants: Women with 16 to 28 weeks pregnancies. Interventions: The sample size was drawn from our 2006-2008 databases and consisted in 278 fetuses 16 to 28 weeks who had ultrasound examination. We categorized two groups: fetuses with isolated short femur (cases) and fetuses with normal femur length (controls). We excluded from analysis fetuses with abnormalities or multiple gestations. Tstudent bivariated analysis was done to compare continuous variables and categorical variables were analyzed by Fisher’s exact test. Main outcome measures: Association of fetal short femur with fetal and maternal complications. Results: Fetuses with isolated short femur showed significantly lower mean birth weight by 412,3 g (p=0,000). Odds ratio for growth restriction was 2,32 (95%CI: 1,03-5,23). Additionally we observed more cases of mothers developing preeclampsia (11,2% vs. 2,1%, p=0,001) and gestational hypertension (11,2% vs. 4,8%, p= 0,046). Also, fetuses with isolated short femur had more frequently 5 minute Apgar score <7 than fetuses with normal femur (4,5% vs. 0,5%, p=0,02). There were two cases of neonatal death in fetuses with isolated short femur. Conclusions: Isolated short femur in second-trimester fetuses is associated with growth restriction, preeclampsia, and gestational hypertension.